2020
DOI: 10.1039/c9fo02475a
|View full text |Cite
|
Sign up to set email alerts
|

Study on the therapeutic material basis and effect of Acanthopanax senticosus (Rupr. et Maxim.) Harms leaves in the treatment of ischemic stroke by PK-PD analysis based on online microdialysis–LC-MS/MS method

Abstract: The therapeutic material basis and effect of ASL in the treatment of ischemic stroke were studied by PK-PD analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…Similarly, microdialysis plays a key role in elucidating disease mechanisms ( Xu et al, 2019 , Xu et al, 2020 , Mever et al, 2020 ; Su et al 2019). (ii) For in vivo single drug studies, microdialysis being applied for PK monitoring and quantification of drugs in skin tissue ( Voelkner et al 2018 ) and plasma ( Girondi et al, 2018 , Wang et al, 2020c ), among others. (iii) For complex component systems, investigators established the study of Ermiao wan metabolites in bile ( Zhao et al, 2020 ) and Mahuang decoction in blood and brain ( Wan et al, 2020 ).…”
Section: Frontier Approaches and Technologies For Pharmacodynamic Sub...mentioning
confidence: 99%
“…Similarly, microdialysis plays a key role in elucidating disease mechanisms ( Xu et al, 2019 , Xu et al, 2020 , Mever et al, 2020 ; Su et al 2019). (ii) For in vivo single drug studies, microdialysis being applied for PK monitoring and quantification of drugs in skin tissue ( Voelkner et al 2018 ) and plasma ( Girondi et al, 2018 , Wang et al, 2020c ), among others. (iii) For complex component systems, investigators established the study of Ermiao wan metabolites in bile ( Zhao et al, 2020 ) and Mahuang decoction in blood and brain ( Wan et al, 2020 ).…”
Section: Frontier Approaches and Technologies For Pharmacodynamic Sub...mentioning
confidence: 99%
“…Установлено, что сочетание методов микродиализа и ВЭЖХ в тандеме с масс-спектрометрией позволяет проводить одновременный и непрерывный количественный анализ нейроактивных веществ в биологической жидкости гиппокампа и плазме, изучая при этом терапевтический эффект активного целевого соединения на бодрствующих ишемизированных крысах [47].…”
Section: Review Articlesunclassified
“…11,12 The fresh fruits and leaves of E. senticosus are edible as seasonal health fare, meanwhile, the dried ESL are usually consumed as tea in Asian countries and have neuroprotective functions in the treatment of disorders of the neural system, such as insomnia, ischemic stroke, and Parkinson's disease. [13][14][15] Our previous research showed that the water-extract of ESL can enhance object recognition memory in normal mice, 16 and some triterpenoid saponins from the water-extract can not only be detected in the brains of treated mice, but also ameliorate amyloid β 25-35induced axonal atrophy of primary cultured neurons. 3,16 We also found that triterpenoid saponins are rich in the waterextract of ESL, in which more than 100 saponins have been characterized based on LC-HR MS analysis, 11 which highlights promising neuroprotective effects in vitro.…”
Section: Introductionmentioning
confidence: 97%